In Pursuit of the Sublime: Ivan Konstantinovich Aivazovsky’s Walking upon the Sea (1849) from the State Art Collection of the Royal Compound in Serbia - Borozan, Igor; Boric, Tijana (Actual Problems of Theory and History of Art, 2016)
The indescribable idea of the sublime fascinated and challenged the famous nineteenth century artist Ivan Konstantinovich Aivazovsky, whose dwelling upon this concept gave rise to countless visual responses. In this paper, we examine the earliest known version of his piece known as Walking upon the Sea, dated 1849, from the State Art Collection of the Royal Compound in Serbia. This particular image is a peculiar combination of the stormy sea at night and religious theme that embodies the artist’s inner self- observations, thoughts, worldview, and the perceptive power of the years to come. Aivazovsky was a man of Romanticism and a visionary genius as well. He was occupied with the ideas of infinity, great drama and of the divine that challenges viewers’ senses of space and time. Walking upon the Sea, the art piece of its time, is a manifest reflection of skepticism of the era, groundbreaking experiments, innovations, and discoveries.
Keywords: Aivazovsky; Romanticism; sublime; skepticism; emotional tuning; deification of nature